E-Money, Product Domestic Bruto, dan Inflasi Terhadap Perputaran Uang Studi Kasus Pada 3 Negara di ASEAN - Annisa Alief Rahmaniar; Dwinita Aryani (BALANCE: Economic, Business, Management and Accounting Journal, 2021)
ABSTRACT   The circulation of money in a country is influenced by several factors, namely e-money, GDP and inflation. The increased use of e-money should be able to increase the circulation of money so that GDP increases and suppresses inflation. The purpose of this research is to determine the effect of electronic money (e-money), Gross Domestic Product (GDP) and inflation on velocity of money in 3 countries in ASEAN using a quantitative descriptive approach. The data analysis technique used is Multiple Linear Regression and using Eviews 9, the population of this study was 324 financial reports from the three countries in ASEAN consisting of Indonesia, Singapore and Malaysia. The results of this study are that e-money, GDP and inflation have a significant effect on the circulation of money in the three countries in ASEAN. Keywords                    : E-money; Gross Domestic Product; Inflation; Velocity of moneyCorrespondence to        : annisarahma17@gmail.com, dwinita@stie-mce.ac.id ABSTRAK Perputaran uang di suatu negara dipengaruhi oleh beberapa faktor yaitu e-money, PDB dan inflasi. Meningkatnya penggunaan e-money seharusnya dapat meningkatkan perputaran uang sehingga PDB meningkat dan menekan adanya inflasi. Tujuan penelitan ini adalah mengetahui pengaruh uang elektronik (e-money), Product Domestic Bruto (PDB) dan inflasi terhadap perputaran uang (velocity of money) pada 3 negara di ASEAN dengan menggunakan pendekatan deskriptif kuantitatif. Teknik analisis data yang digunakan Regresi Linear Berganda dan menggunakan Eviews 9, populasi penelitian ini yaitu 324 laporan keuangan dari ketiga negara di ASEAN yang terdiri dari Indonesia, Singapura dan Malaysia. Hasil penelitian ini adalah e-money, PDB dan inflasi memiliki pengaruh signifikan terhadap perputaran uang pada ketiga negara di ASEAN.Kata Kunci                  : Uang elektronik; PDB; Inflasi; Perputaran uang